2013
DOI: 10.1097/pas.0b013e31826a92f5
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary Solitary Fibrous Tumors

Abstract: Solitary fibrous tumor (SFT) is a ubiquitous neoplasm that arises most commonly from the pleura. SFT arising within lung parenchyma (intrapulmonary SFT) has been rarely reported and is therefore not well recognized. We present a clinicopathologic and immunohistochemical study of 24 cases of primary intrapulmonary SFT. Patients' ages ranged from 44 to 83 years (mean, 58 y). None of the patients had evidence or history of a similar tumor elsewhere. Tumor size ranged from 2.3 to 22 cm (mean, 8.5 cm). On the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(32 citation statements)
references
References 54 publications
(50 reference statements)
2
25
0
Order By: Relevance
“…SFT typically appear as masses abutting the pleura; most often arising from the lung visceral pleura (≈80% of cases) (13), but occasionally with apparent origins from the mediastinal (≈1-8% of cases) or parietal pleura (2,12,13,16,17). Given the close proximity of the various pleural surfaces to each other, the precise origin/extent of these lesions can be uncertain (Figure 1,2,3,4).…”
Section: Radiologymentioning
confidence: 99%
“…SFT typically appear as masses abutting the pleura; most often arising from the lung visceral pleura (≈80% of cases) (13), but occasionally with apparent origins from the mediastinal (≈1-8% of cases) or parietal pleura (2,12,13,16,17). Given the close proximity of the various pleural surfaces to each other, the precise origin/extent of these lesions can be uncertain (Figure 1,2,3,4).…”
Section: Radiologymentioning
confidence: 99%
“… 4 10 An SFTs diagnosis is characterized by the proliferation of spindle mesenchymal cells and positive immunohistochemical staining for CD34. 11 , 12 Approximately 78% to 88% of SFTs are benign, but 12% to 22% are malignant. 13 , 14 The age-standardized incidence of SFTs is reported to be 1.4 per million 15 and their rarity, diverse localizations, and difficulty of predicating tumor biological behaviors have limited the attempts to obtain CT and MRI data to better characterize their features.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have confirmed that tumor markers, including CD34 + , Bcl-2 + and CD99 + , are generally positive in SFT cases, which has aided the diagnosis of SFTs ( 17 , 18 ). Currently, the positive staining of CD34 + is indispensable in the diagnosis of an SFT; however, the expression of CD34 is not limited to SFTs ( 11 ).…”
Section: Discussionmentioning
confidence: 78%
“…Usually, an SFT is defined as a benign form of tumor due to its low rates or even absence of local recurrence and metastasis, as demonstrated by a number of previous studies ( 1 , 2 , 22 , 23 ). However, an increasing number of recent studies have demonstrated that a considerable number of SFTs are malignant ( 11 , 18 , 24 ). In the case of an SFT which is unresectable, metastatic or has positive surgical margins, patients are unlikely to benefit significantly from radiotherapy or chemotherapy; the alternative treatments for an SFT ( 2 ).…”
Section: Discussionmentioning
confidence: 99%